Avaliação de cereais de inverno de duplo propósito na depressão central do Rio Grande do Sul - Meinerz, Gilmar Roberto (2009)
In the south of Brazil, one of the largest limitations of cattle activity is the forage lack in the autumn and beginning of winter, causing decrease in milk and meat production. One of the alternatives to minimize this problem is the use of double-purpose winter cereals, that they can supply early green forage and still to produce grains. Then, the objective of this research was to evaluate early growth, forage yield and nutritive value, grains and silage yield of 12 genotypes of six double purpose winter species, submitted to harvest at Depressão Central region of Rio Grande do Sul state. Species and genotypes tested were: BRS 277, BRS Guatambu, BRS Tarumã and BRS Umbu wheat; Agro Zebu, UPFA 21 - Moreninha and Commom black-oat; UPF 18 white oat; BR 1 and BRS Serrano rye; BRS Marciana barley; and BRS 148 triticale. The genotypes were distributed in 36 experimental plots in completely randomized design, with 12 treatments and three replications. Studied variables were herbage mass, botanical and structural composition, forage and grains production. Samples of the superior stratum to 10 cm height of forage were used to nutritive value analysis. Near infrared spectroscopy (NIRS) technique was used to determine contents of crude protein, insoluble neutral detergent fiber, insoluble acid detergent fiber, dry matter digestibility and minerals calcium, phosphorus, magnesium and potassium. Also were evaluated yield and nutritive value of silage on different genotypes in soft dough grain stage. Early genotypes for forage production were BR 1 rye and BRS 148 triticale. BRS Tarumã wheat presented higher leaf blade and forage yield. BRS Umbu wheat presented higher grains production and hectoliter weight. Oat genotypes present best nutritive value results and mineral composition presents small variability among tested genotypes. Higher pre-ensilage forage production was observed to BR 1 rye and UPF 18 white oat and BRS Umbu wheat has the best nutritive value of silage. Results demonstrate that winter cereals produced early forage with high nutritive value and presents satisfactory conditions to silage production.